Hubungan antara agama dan ekonomi - Khanifah, Nuha Nafi’atul (Maliki Interdisciplinary Journal, 2025)
Studies on the relationship between religion and economics show that religion is not only a belief system, but also functions as a social institution that shapes norms, ethics, and economic behavior of individuals and society. Thinkers such as Weber, Durkheim, and Geertz highlight how religious teachings play a role in building work ethics, regulating the distribution of resources, and influencing economic policies. Islam, Christianity, and Judaism instill moral values such as honesty, justice, and social responsibility in economic activities. In addition, religion contributes to social welfare through concepts such as zakat in Islam and oikonomia in Christianity. Although modern economics focuses more on the material aspect, a religion-based approach provides balance by considering the spiritual aspect. By adopting religious principles in the economic system, it is hoped that an economic order will be formed that is more ethical, just, and supports the welfare of society as a whole.